IMPLEMENTATION OF DISCHARGE PLANNING BY HEALTH PERSONNEL IN VIOLENT BEHAVIOR PATIENTS - Masdiana AR; Maryati Tombokan; Sri Angriani; Subriah Subriah (Bajang Institute, 2022)
The application of discharge planning in patients with violent behavior is an approach taken by nurses to families or clients so that it is hoped that the recurrence rate in patients with violent behavior is expected to decrease Objective : This literature study aims to identify the application of discharge planning in every journal article of health workers in the treatment of violent behavior patients. Research Methods : Using the literature strategy method and identifying 10 journals that meet the criteria according to the inclusion criteria with a time span from 2013-2022. Results and Analysis : The result show that the administration of discharge planning is proven to be affective in rate in patients with violent behavior. Discussion and Conclusions : The implementation of discharge planning is quite effective in reducing the reccurence of violent behavior after discharge from the hospital. The decrease in the recurrence rate at home can be influenced by several factors, including the frequency of exercise that have been taught by nurses to patients while in hospital and when the patient is about to go home, respondent characteristics, coping abilities, family and environmental support.